English Language Needs for Workplace Communication in Makassar's Health and Tourism Sectors: An ESP Needs Analysis - Nadya Nurhidayah N (EDULEC : Education, Language, and Culture Journal, 2026)
This study identifies English for Specific Purposes (ESP) needs related to workplace communication among health and tourism practitioners in Makassar, Indonesia. A sequential explanatory mixed-methods design was used to combine a quantitative needs survey with qualitative stakeholder interviews. The quantitative phase involved 100 purposively selected practitioners in international-facing health and tourism roles. A 25-item Likert-type questionnaire examined professional tasks, linguistic skills, and perceived competence. The qualitative phase involved semi-structured interviews with 10 stakeholders, five from each sector, to explain the communication difficulties underlying the survey priorities. Quantitative data were summarized using frequencies and percentages, while interview data were analyzed thematically and integrated with the survey results. Four priority task domains were identified: clinical and technical interaction (28%), front-line logistics (27%), operational safety (24%), and affective communication (21%). Clinical anamnesis, procedure explanation, safety briefings, directions, complaint handling, and culturally appropriate interpersonal communication emerged as central workplace demands. Interview accounts further indicated difficulties with rapid spoken English, unfamiliar accents and idioms, technical vocabulary, and pragmatic strategies such as hedging and softening language. The combined clinical and safety categories represented 52% of identified needs, highlighting the importance of accurate oral communication in high-stakes encounters. The findings support locally responsive, task-based ESP training built around authentic simulations, listening practice, professional phraseology, and pragmatic communication. Because the study used purposive sampling and descriptive analysis in one city, the findings should be interpreted as context-specific priorities rather than population estimates.